Development of Direct Models for Percent Time-Spent Following on Two-Lane Highways - Ahmed, Faisal; Easa, Said M. (Frontiers in Built Environment, 2020)
The percent time-spent following (PTSF) is a key measure for estimating the level-of-service for two-lane highways. However, PTSF is currently estimated indirectly using various measured field data. This study proposes two alternative direct models for estimating PTSF: (1) a general linear regression model using typically-used input variables and (2) a non-linear form using only the follower density. Both models are based on data generated from the corridor micro-simulation (CORSIM) software. Comparison of the proposed models with the new directional PTSF analytical model of the Highway Capacity Manual shows that the proposed models are capable of predicting simulation-generated PTSF quite closely with absolute mean error <3% using two different sets of validation datasets. The results of this research would be useful for a convenient and direct estimation of directional PTSF of two-lane highways.